Increased Expression of Plasma miRNA-320a and let-7b-5p in Heroin-Dependent Patients and Its Clinical Significance - Liu, Haixiong; Xu, Wenjin; Feng, Jiying; Ma, Hong; Zhang, Jianbin; Xie, Xiaohu; Zhuang, Dingding; Shen, Wenwen; Liu, Huifen; Zhou, Wenhua (Frontiers in Psychiatry, 2021)
Heroin use disorder is a chronic and relapsing disease that induces persistent changes in the brain. The diagnoses of heroin use disorders are mainly based on subjective reports and no valid biomarkers available. Recent researches have revealed that circulating miRNAs are useful noninvasive biomarkers for diagnosing brain diseases such as Alzheimer’s disease, multiple sclerosis, schizophrenia, and bipolar disorder. However, studies on circulating miRNAs for the diagnosis of heroin use disorders are rarely reported. In this study, we investigated the differential expression of plasma miRNAs in 57 heroin-dependent patients. Based on literature research and microarray analysis, two candidate miRNAs, miR-320a and let-7b-5p, were selected and analyzed by quantitative real-time RT-PCR. The results showed miR-320a and let-7b were significantly upregulated in plasma of the heroin-dependent patients compared to that in healthy controls. The area under curves (AUCs) of receiver operating characteristic (ROC) curves of miR-320a and let-7b-5p were 0.748 and 0.758, respectively. The sensitivities of miR-320a and let-7b-5p were 71.9% and 70.2%, while the specificities of miR-320a and let-7b-5p were 76.1% and 78.3%, respectively. The combination of these two miRNAs predicted heron dependence with an AUC of 0.782 (95% CI 0.687–0.876), with 73.7% sensitivity and 82.6% specificity. Our findings suggest a potential use for circulating miRNAs as biomarkers for the diagnosis of heroin abuse.